Measurement of Central Aortic Blood Pressure in Youth: Role of Obesity and Sex - Harbin, Michelle M (Am J Hypertens, 2018)
BACKGROUND: The relationship between pediatric severe obesity (SO) and central aortic blood pressure (BP) has yet to be established. METHODS: We conducted a cross-sectional study of 348 youth (48.5% male, age 12.7 ± 0.1 years) with a wide range of body mass index (BMI) values: normal weight (NW; ≥5th and <85th BMI percentiles), overweight/obesity (OW/OB; 85th to <120% of the 95th BMI percentile), and SO (≥120% of the 95th BMI percentile). Measures of central aortic BP were obtained via applanation tonometry with SphygmoCor MM3 software. RESULTS: After adjustment for covariates, no significant sex differences were observed for radial−aortic systolic blood pressure (SBP) (P = 0.39), carotid−aortic SBP (P = 0.99), radial−aortic diastolic blood pressure (DBP) (P = 0.44), and carotid−aortic DBP (P = 0.53). Compared to youth with NW, youth with SO exhibited higher radial−aortic SBP (SO vs. NW: 102 ± 1 mm Hg vs. 90 ± 1 mm Hg, P<0.001), carotid−aortic SBP (SO vs. NW: 121 ± 1 mm Hg vs. 109 ± 1 mm Hg, P<0.001), and carotid−aortic DBP (SO vs. NW: 60 ± 1 mm Hg vs. 56 ± 1 mm Hg, P = 0.04). Compared to youth with OW/OB, youth with SO had higher radial−aortic SBP (OW/OB: 97 ± 1 mm Hg, P = 0.002) and carotid−aortic SBP (OW/OB: 114 ± 1 mm Hg, P = 0.007). After adjusting for either total-body percent fat mass or visceral adipose tissue, BMI was still a significant predictor of both radial−aortic and carotid−aortic SBP and DBP (P<0.001, all). CONCLUSIONS: In a cohort of youth with a wide range of adiposity levels, central aortic BP was elevated among individuals with SO and associated with BMI but not body fatness.